Mobile Phone Addiction and its Relationship with Selfdiscloser among Sample of Students from University of Jordan and Amman Al-Ahliyya University - Abu-Jedy Aِmjad (Jordan Journal of Educational Sciences, 2008)
The purpose of the study is to investigate addiction to mobile phone and its relationship with self-discloser among sample of students selected from the university of Jordan and Amman Al-Ahliyya University. It also looks at the characteristics of addicted persons، highlighting the main aspects of their addiction، for what purposes mobile phones are used، and the time spent in using mobile phones. To achieve study goals، the researcher developed mobile phone addiction scale، which had an appropriate validity and reliability indexes، a sample of (480) male and female students were selected during the first semester in 2006\2007 academic year. The data analysis revealed the following results: − Addicted persons comprised (25،8%) of the total sample. − The percent of addicted females was twice as more than males. − There is a significant difference in terms of addiction related to the field of study. Students of humanities have higher addiction level than natural science students. − There is a higher level of addiction amongst private university students and public university students. − There is a significant relationship between mobile phone addiction and self-discloser، the correlation coefficient was(0.668)